The Context of Traditional Medicine in Contemporary Times: the Case of Bafut in the North West Region of Cameroon - Dieudonne, NEBANE (IJRDO - Journal of Social Science and Humanities Research, 2021)
Bafut has been more and more a medically plural society, especially after many years that WHO published that about 80% of Africans are using traditional medicine for their health needs. This article seeks to examine the place and status of African traditional medicine in the context of medical pluralism and also evaluating the importance of traditional medicine in Bafut. This study which is essentially qualitative was conducted to a greater extent in Bafut and to a lesser extent in Yaounde in 2010 and 2011. The methods included observation, in-depth interviews, and informal discussions. We interviewed 15 people, 5 conventional medical practitioners and 10 traditional healers. Our analyses are based on some social scientific theories and themes. Traditional medicine in Bafut is facing competition from conventional medicine and faith healing. The influence of Western medical ideology, Western religious practices, and educational levels also impact traditional medicine. Most traditional healers are dying without transmitting their knowledge to the younger generations, hence, posing a question about its future existence. Traditional medicine must be protected for posterity because of its impact on health care.